Manajemen Pendidikan Karakter Berbasis Panca Cinta pada Anak Usia Dini - Hamzatul Munir; Rizki Novita (Tanwiruna: Jurnal Pendidikan dan Sosial Keagamaan, 2026)
Strengthening character education in Early Childhood Education (PAUD) requires systematic governance so that moral-spiritual values do not stop at slogans, but are internalized in learning habits and institutional culture. This study aims to describe and analyze the management of Panca Cinta-based character education in early childhood, including planning, organizing, implementing, and supervising programs, as well as their supporting and inhibiting factors. The method used is qualitative with a case study Design through in-depth interviews, observation of learning activities and school culture, and documentation studies. The data is analyzed thematically. The results of the study show that the implementation of Panca Cinta is effective when integrated into the curriculum and daily routine (habituation, example, and behavior strengthening), supported by institutional leadership, teacher collaboration, and parent partnerships. The main obstacles arise from inconsistent implementation, limited resources, and unstandardized evaluation. This research contributes to the development of a practical value-based management framework for early childhood education, as well as to the implications of strengthening character development policies, teacher training, and sustainable monitoring systems.